The Influence of Perceived Organizational Support and Work-Life Balance on Turnover Intention Through Job Satisfaction - Nurul Fitrianis Naini; Setyo Riyanto (International Journal of Islamic Business and Management Review, 2023)
This study aims to analyze the effect of Perceived Organizational Support and Worklife Balance on Turnover Intention through Job Satisfaction as a Mediation variable. In this research, PT ABB's permanent employees with a total sample of 62 (sixty two) employees. The data analysis method uses Structural Equation Model-Partial Least Square (SEM-PLS) with SmartPLS 4.0. The results of the study found that Perceived Organizational Support had a positive and significant effect on Job satisfaction, Work-Life Balance had a positive and significant effect on Job Satisfaction, Work-Life Balance had a significant effect on Turnover Intention, Job Satisfaction had a positive but not significant effect on Turnover Intention, Perceived Organizational Support has a positive but not significant effect on Turnover Intention, Perceived Organizational Support has a Positive but Not Significant effect on Turnover Intention through Job Satisfaction. Work-Life Balance has a positive but not significant effect on Turnover Intention through Job Satisfaction. Company leaders are advised to increase Perceived Organizational Support and Work-Life Balance to increase Job Satisfaction which can affect Turnover Intention.